The Effect of Composition, Pyrolysis Temperature and Adhesive Concentration on the Proximate Content and Calorific Value of Biobriquettes from Durian Skin, Corn husk and Fish Bones Waste - Nora Amelia Novitrie; Vivin Setiani; Aisyah Dinda Camalia (Universitas Diponegoro, 2023)
Briquettes are an alternative energy derived from biomass. Biomass material can be obtained from plantation waste such as durian peel, agricultural waste such as corn husk and waste from the fisheries sector such as fish bones. Waste of corn husks, durian peel and fish bones have the potential to become biomass material as an alternative energy. The aim of this research is to analyze the effect of variations in composition, pyrolysis temperature and adhesive concentration on the quality of biobriquettes and emissions resulting from the combustion process. The dried waste materials is then pyrolyzed for 4 hours at 350 ℃ and 500 ℃. Proximate testing was carried out to determine the quality of the biobriquettes. The parameters analyzed in this test include moisture content, ash content, volatile matter content, bound carbon content and heating value. The results of the study revealed that the best sample variations were found in briquettes with a composition of 50% durian peel [T1] [c2] : 50% corn husk with a pyrolysis temperature of 350℃ and an adhesive concentration of 7%. The level of CO emissions produced when burning briquettes is 1,700 mg/Nm3 and SO2 is 0.741 mg/Nm3.